Perancangan Sistem Arsip Data Digital Menggunakan Model Waterfall Berbasis Web - Gagah Dwiki Putra Aryono; Bima Prasetya; Sigit Auliana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research aims to design a digital data archiving system at PT Perkebunan Nusantara Regional I Kebun Cisalak Baru. This system was developed to replace the existing manual process, making archive management faster, easier, and more secure. The system was built using PHP Native and MySQL, and tested using the black box method to ensure its functionality runs smoothly. The development results show that the system is able to manage archive data effectively, from input and search to report printing. With this system, administrative processes become more efficient and organized.